Hubungan diabetes mellitus dengan obstructive sleep apnea (OSA) di Gedung Mario Tabanan, Bali-Indonesia - Tince Sarlin Nalle; I Dewa Gede Arta Eka Putra (Intisari Sains Medis, 2021)
Background: Diabetes mellitus (DM) is a chronic case caused by the pancreas not being able to produce insulin and when there is insulin resistance. This disease is characterized by a lot of drinking, eating, weight loss and frequent urination. This drastic weight loss results in a decrease in body mass, one of which is the nasopharynx and oropharynx so that it can cause collapse and cause Obstructive sleep apnea (OSA). This study aims to determine whether there is a relationship between diabetes mellitus and OSA in the social service held at the Mario Tabanan building on June 16, 2008.Methods: An observational analytic study with cross sectional design with a sample of 110 people. This study was conducted at Mario Building, Tabanan, Bali, Indonesia.Results: A total of 110 samples were successfully collected in this study, with an age range of 50-70 years, 55 patients with diabetes mellitus (DM) and 55 patients without diabetes. From the research above, it was found that there were more men than women, namely 67 people (58.3%) and women amounting to 43 people (42.7%). The average age who received OSA was 57.35 ± 10.89. The results of the study of the prevalence of patient respondents who suffered from DM with OSA were 65 people (53.5%) and patients who did not suffer from DM were 45 (46.5) and patients who did not have DM with OSA were 46 people (47.8%), and those who did not have diabetes and no OSA were 64 people (52.2%). There was a significant relationship between OSA and DM with a p value <0.05 and the prevalence ratio value was the Prevalent Ratio (RP) 1.432 with a confidence interval (1.024 to 5.980).Conclusion: Diabetes is a risk factor for OSA, and there is a significant relationship between diabetes and the incidence of OSA. Latar Belakang: Diabetes mellitus (DM) merupakan kasus kronis yang diakibatkan pankreas tidak mampu memproduksi insulin dan ketika ada resistensi insulin. Penyakit ini ditandai dengan banyak minum, makan, berat badan turun drastis dan sering buang air kecil. Penurunan berat badan drastis ini mengakibatkan penurunan massa otot tubuh salah satunya adalah nasofaring dan orofaring sehingga dapat menyebabkan kolaps dan menimbulkan terjadinya Obstructive sleep apnea (OSA). Penelitian ini bertujuan mengetahui apakah ada hubungan antara diabetes mellitus dan OSA pada baksos yang diadakan di gedung Mario Tabanan pada tanggal 16 Juni 2008.Metode: Penelitian analitik observasional dengan rancangan cross sectional dengan sampel sebanyak 110 orang yang dilakukan di Gedung Mario Tabanan, Bali, Indonesia.Hasil: Total 110 sampel berhasil dikumpulkan dalam penelitian ini, dengan rentangan usia 50-70 tahun, 55 pasien dengan diabetes mellitus (DM) dan 55 pasien tidak DM. Dari penelitian diatas didapatkan laki-laki lebih banyak daripada perempuan yaitu 67 orang (58,3%) dan perempuan berjumlah 43 orang (42,7%). Rata rata umur yang mendapatkan  OSA 57,35± 10,89. Hasil penelitian prevalensi responden pasien yang menderita DM dengan OSA adalah 65 orang (53,5%) dan, pasien yang tidak menderita DM adalah sejumlah 45 (46,5) dan pasien yang tidak DM dengan OSA adalah sejumlah 46 orang (47,8%) dan yang tidak DM dan tidak OSA adalah 64 orang (52,2%) Didapatkan adanya hubungan signifikan antara OSA dengan DM dengan nilai p<0,05 dan nilai rasio prevalens adalah Rasio Prevalen (RP) 1,432 dengan interval kepercayaan (1,024 sampai 5,980).Simpulan: Diabetes merupakan faktor risiko dari terjadinya OSA, dan didapatkan hubungan yang bermakna antara diabetes terhadap kejadian OSA.